Miskonsepsi Siswa SMA Tentang Gerak dan Gaya Menggunakan Instrumen Force Concept Inventory (FCI) - Rini Khoirunnisa; Syuhendri; Kistiono; Mardiah Afifa (Postgraduate, University of Mataram, 2024)
This research aims to identify high school students' misconceptions regarding motion and force using the Force Concept Inventory (FCI) instrument. This study used a quantitative method with respondents of 108 students in class XI science. Misconception data was obtained using FCI in the form of multiple-choice questions. There are 30 questions with five options. The results showed that a total of 46 out of 108 students (19.44%) answered 8 to 11 questions correctly, 41 students (37.96%) answered 5 to 7 questions correctly and the other 21 students (42.59%) only answered 2 to 4 questions correctly. The conclusion is students had misconceptions about the concepts of motion and force, especially on topics such as kinematics, Newton's laws, the principle of superposition, and kinds of force. This research implies the importance of understanding students' misconceptions in developing physics curricula and learning strategies in high schools. It is hoped that the research results can provide information to teachers about students' conceptual understanding so that appropriate learning strategies can be developed to correct students' misconceptions in learning.